Optimasi Rute Pengiriman Produk dengan Meminimumkan Biaya Transportasi Menggunakan Metode Saving Matrix di PT. DEF - Elfiani Sarian Bur; Dewi Murni; Yenni Kurniawati (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Decreasing water of systim water supplier factory represents difference the distribution value with consumption value. This case is used as a benchmark to the efficiency of the distribution system by the development of system water supplier factory. This cases can cause disadvantages to the systim water supplier factory. Therefore in the next few years, this case needs to be forecasting that the systim water supplier factory has plans and appropriate action in order to the minimaze it. This research is to obtain a forecasting model and predict decreasing water of system water supplier factory Padang Panjang city in2015 until 2019. The forecasting method used is triple exponential smoothing of brown type. The parameter α is used 0.128 which gives the value of Mean Square Error (MSE), that the smallest is 8.0892145076 ×1010. Forecasting of decreasing water system water supplier factory from 2015 to 2019 ranged from 1402382,354m3to1757709,053m3 . Keywords – Water decrease, Forecasting, Exponential Smoothing Triple Brown Type, Mean Square Error (MSE).